2017
DOI: 10.1371/journal.pone.0175038
|View full text |Cite
|
Sign up to set email alerts
|

Access to percutaneous transluminal coronary angioplasty and 30-day mortality in patients with incident STEMI: Differentials by educational level and gender over 11 years

Abstract: BackgroundSocioeconomic status and gender are associated with access to cardiac procedures and mortality after AMI, also in countries with universal health care systems. Our objective was to evaluate the association and trends of educational level or gender and the following outcomes: 1) access to PTCA; 2) 30-day mortality.MethodsWe conducted an observational study based on 14,013 subjects aged 35–74 years, residing in Rome in 2001, and hospitalised for incident STEMI within 2012 in the Lazio region. We estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Instead, we observed a considerable improvement among the least educated patients, which helped to fill the equity gap in terms of access to effective treatment attributable to educational level. Cacciani et al [ 27 ] had already reported a similar result after observing a decreasing educational differential in the access to PCI between 2001 and 2011, using data from a cohort of STEMI residents in Rome (Italy). This finding seems to suggest that the efforts of the health system in improving health care quality could also be effective in improving equity.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Instead, we observed a considerable improvement among the least educated patients, which helped to fill the equity gap in terms of access to effective treatment attributable to educational level. Cacciani et al [ 27 ] had already reported a similar result after observing a decreasing educational differential in the access to PCI between 2001 and 2011, using data from a cohort of STEMI residents in Rome (Italy). This finding seems to suggest that the efforts of the health system in improving health care quality could also be effective in improving equity.…”
Section: Discussionmentioning
confidence: 63%
“…However, only a few studies have demonstrated whether an overall improvement in the quality of care has had a differential impact on different subgroups of the population [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical characteristics, vital signs and Killip class were fairly consistent across periods, patients in the postoutbreak time were about 5 years younger and had a 13-point lower percentage of female, comparing those in the outbreak time. Although the explication of reasons for these changes is beyond the scope of our study, a number of prior studies pointed out the fact that elderly and female patients with STEMI have higher in-hospital mortality or worse clinical outcomes than the young and the male 29 30. Nevertheless, data of our study provide additional information that neither the risk profile of patients hospitalised with STEMI has significantly changed in the postoutbreak time and nor have the clinical outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Sex disparities in other cardiovascular diseases suggest that such finding may also derive from reasons not specific to VTE. Studies from Italy report higher post-ST-segment elevation myocardial infarction mortality and lower use of percutaneous coronary intervention in women than in men, 25,26 and, in line with international literature, 27 attribute the difference to older age at presentation as well as to treatment delay or suboptimal treatment among women. Both explanations may also apply to death from PE.…”
Section: Discussionmentioning
confidence: 78%